READAPTAÇÃO DOCENTE: TRAJETÓRIA PROFISSIONAL E IDENTIDADE - Antunes, Sandra Maria Pateiro Salgado Noveletto (2014)
This research, through privileged references and field research seeks to understand and show if there are or not there are absences of teachers with diseases of psychic origin of their roles (re-adaptation) for reasons not merely physiological, but that stems from social nature, in other words, if is there a social motive that cause this phenomenon in the educational system . Also, understand if the teacher has a critical consciousness of these possible causes and how is your identity after the re-adaptation. The social and economic changes that have occurred in recent decades due to successive crises and restructuring of capitalism influenced the educational context as well as the working conditions of teachers, interfering in physical and psychological health of teachers. Through an overview of current working conditions and health of teachers, arising from the process of easing and precariousness of labor relations in education. We try to explain, having as theoretical Sennett (2001) and Esteve (1999) among others, the new reality of work and discomfort experienced by teachers in educational institutions. The field research denotes the trajectory of teachers readapted from their working conditions that permeates the difficulties, obstacles, and malaise until the moment of illness and finally the situation of re-adaptation. The problems experienced by readapted teachers has an impact over their professional identity because the teachers are marked by stigma, discrimination, feelings of blame yourself, social devaluation, which impairs their quality of life and interpersonal relationships, both at work and in the family. The research shows that the illness psychic affects seriously the teaching professional. This situation is serious in the public schools of São Paulo and demonstrates that it is important to recognize the need for public and educational policies that gives value teaching and health of this professional category .